Adjustment of Code Ranging of GNSS Observations - Jana Izvoltova; Peter Pisca; Pavel Cernota; Marian Mancovic (Communications - Scientific letters of the University of Zilina, 2016)
Gauss-Jacobi combinatorial algorithm is a very useful method to adjust code ranging of global navigation satellite observations to find the systematic errors caused by radio waves passing through the atmosphere. The method is used as alternative adjustment technique to the least square method. While, the least square adjustment requires the linearization of nonlinear functions, combinatorial approach seems to be simplier in direct processing the nonlinear models. The diagnostics of observation errors consists in comparison of an evaluated partial positional norm determined in the partial mathematical models with the global one determine by robust estimation.